Utility of objective gait measures in levodopa‐unresponsive freezing in Parkinson's. Issue 3 (13th January 2021) - Virmani, Tuhin; Glover, Aliyah; Pillai, Lakshmi; Lotia, Mitesh; Dhall, Rohit
Abstract: Levodopa‐unresponsive gait freezing in Parkinson disease is debilitating. Gait kinematics, while time‐consuming, can help optimize levodopa's benefit on gait stride length and stride velocity, and thereby improve freezing and falls in these patients. Abstract : Levodopa‐unresponsive gait freezing in Parkinson disease is debilitating. Gait kinematics, while time‐consuming, can help optimize levodopa's benefit on gait stride length and stride velocity, and thereby improve freezing and falls in these patients.